Natural and Activated Allophane Catalytic Activity Based on the Microactivity Test in Astm Norm 3907/D3907M-2019 - Edward Henry Jiménez Calderón; Ana Emperatriz Paucar Tipantuña; Paulina Fernanda Herrera Mullo; Daniel Alejandro Hidalgo Cháfuel; Washington Ruiz; Ullrich Stahl; José Bermudez (Applied Sciences, 2020)
The optimal conditions of the catalytic activation of allophane were evaluated for possible use as a catalyst within a fluidized bed catalytic cracking unit (FCC). The physicochemical properties of natural allophane and activated allophane were studied by using an alkaline activating agent, followed by a hydrothermal treatment. For the characterization, analytical techniques were used: Fourier transform infrared spectroscopy, particle size, (BET) surface area, thermogravimetry (TGA), X-ray diffraction (XRD), chemisorption, X-ray fluorescence (XRF), atomic force microscopy (AFM), and chromatography. The catalytic evaluation was determined by the (MAT) micro activity test equipment constructed according to ASTM D-3907/D3907M-2019. In addition, the Navier–Stokes 3D equations (nonlinear partial derivatives) were studied, which allow studying molecular dynamics contributing substantively to chemical kinetics describing the process of decomposition of crude oil in thermal cracking, determining the maximum temperature at which it retains its properties through the action of heat.